Sistem Monitoring pH, Suhu, dan Pakan Otomatis pada Budidaya Lobster Air Tawar Berbasis IoT Menggunakan Metode K-NN - Shifa Anamika; Warta, Joni; Prio Kustanto (Journal of Informatic and Information Security, 2022)
This study aims to design an automated system tool for freshwater crayfish aquaculture based on the Internet of Things (IoT). In lobster cultivation, it is necessary to pay attention to important factors for the success of cultivation, namely environmental conditions, feed and water quality. Water quality that must be considered from the water temperature and pH of the water. In thisautomatic system, sensors are made that can monitor pH, temperature and feed automatically. The design of this tool for monitoring pH, temperature and feed can be controlled through the Blynk application and using the K-Nearest Neighbor (K-NN) method can help in calculating the distance to the expected water quality. The tool made can be run remotely with a micro device called Wemos D1 as the central controller which is connected to the application and the temperature sensor used is a Thermocouple and a pH meter sensor. With this automatic system tool, it can be used properly so that it can produce lobster with good quality.